Techno-economic assessment of rooftop solar photovoltaic integration for institutional energy efficiency and sustainability enhancement - Iriyanto, Sofyan Dwi; Rehiara, Adelhard; Rumengan, Yanty (Institute for Advanced Science Social, and Sustainable Future, 2025)
Background : This study investigates the technical and economic feasibility of an on-grid rooftop solar photovoltaic (PV) system for the Postgraduate Building of the University of Papua, West Papua, Indonesia. Amid rising energy demands and limited renewable energy utilization in the region, this research addresses the need for sustainable electricity solutions. Methods: The system was designed using Helioscope software, considering solar radiation, shading, and local climate data. The proposed configuration consists of 14 polycrystalline solar modules (320 Wp each) and one SMA Sunny Tripower 5.0 kW inverter. Results: Simulation results indicate that the system can produce approximately 5,660 kWh annually, covering 19% of the building’s electricity consumption. The estimated initial investment of Rp 137,200,000 yields annual savings of Rp 9,617,740, resulting in a payback period of 14 years and 2 months. Conclusion: The findings demonstrate the viability of rooftop solar power systems for reducing energy costs and enhancing sustainability in remote areas. The project serves as a replicable model for academic institutions seeking to adopt renewable energy technologies. Novelty: This study provides a localized case of solar PV deployment in West Papua, contributing empirical insights to regions with limited renewable energy integration and offering a practical approach to energy transition in underserved areas.